The answer is 2/11 in simplest form
Answer:
10010
Step-by-step explanation:
![1011=1(2)^3+0(2)^2+1(2)^1+1(2)^0](https://tex.z-dn.net/?f=1011%3D1%282%29%5E3%2B0%282%29%5E2%2B1%282%29%5E1%2B1%282%29%5E0)
![111=1(2)^2+1(2)^1+1(2)^0](https://tex.z-dn.net/?f=111%3D1%282%29%5E2%2B1%282%29%5E1%2B1%282%29%5E0)
So
gives us:
![1(2)^3+0(2)^2+1(2)^1+1(2)^0](https://tex.z-dn.net/?f=1%282%29%5E3%2B0%282%29%5E2%2B1%282%29%5E1%2B1%282%29%5E0)
![+](https://tex.z-dn.net/?f=%2B)
![1(2)^2+1(2)^1+1(2)^0](https://tex.z-dn.net/?f=1%282%29%5E2%2B1%282%29%5E1%2B1%282%29%5E0)
-----------------------------------------------------
Combine like terms:
![1(2)^3+(0+1)(2)^2+(1+1)(2)^1+(1+1)(2)^0](https://tex.z-dn.net/?f=1%282%29%5E3%2B%280%2B1%29%282%29%5E2%2B%281%2B1%29%282%29%5E1%2B%281%2B1%29%282%29%5E0)
![1(2)^3+1(2)^2+(2)(2)^1+(2)(2)^0](https://tex.z-dn.net/?f=1%282%29%5E3%2B1%282%29%5E2%2B%282%29%282%29%5E1%2B%282%29%282%29%5E0)
We aren't allowed to have a coefficient bigger than 1.
I'm going to replace
with 1 and
with
:
![1(2)^3+1(2)^2+(2)^2+(2)^1(1)](https://tex.z-dn.net/?f=1%282%29%5E3%2B1%282%29%5E2%2B%282%29%5E2%2B%282%29%5E1%281%29)
I want a
number:
![1(2)^3+1(2)^2+1(2)^2+1(2)^1+0(2)^0](https://tex.z-dn.net/?f=1%282%29%5E3%2B1%282%29%5E2%2B1%282%29%5E2%2B1%282%29%5E1%2B0%282%29%5E0)
Combine like terms:
![1(2)^3+2(2)^2+1(2)^1+0(2)^0](https://tex.z-dn.net/?f=1%282%29%5E3%2B2%282%29%5E2%2B1%282%29%5E1%2B0%282%29%5E0)
:
![1(2)^3+2^3+1(2)^1+0(2)^0](https://tex.z-dn.net/?f=1%282%29%5E3%2B2%5E3%2B1%282%29%5E1%2B0%282%29%5E0)
Combine like terms:
![2(2)^3+1(2)^1+0(2)^0](https://tex.z-dn.net/?f=2%282%29%5E3%2B1%282%29%5E1%2B0%282%29%5E0)
We can rewrite the first term by law of exponents:
![2^4+1(2)^1+0(2)^0](https://tex.z-dn.net/?f=2%5E4%2B1%282%29%5E1%2B0%282%29%5E0)
![1(2)^4+1(2)^1+0(2)^0](https://tex.z-dn.net/?f=1%282%29%5E4%2B1%282%29%5E1%2B0%282%29%5E0)
So the binary form is:
![10010](https://tex.z-dn.net/?f=10010)
Maybe you like this way more:
Keep in mind 1+1=10 and that 1+1+1=11:
Setup:
1 0 1 1
+ 1 1 1
------------------------------
(1) (1) (1)
1 0 1 1
+ 1 1 1
------------------------------
1 0 0 1 0
I had to do some carry over with my 1+1=10 and 1+1+1=11.
Answer:
26/20
Step-by-step explanation:
y2-y1 divided by x2-x1
4-24= -20
3-29= -26
-20/-26= m
perpendicular means to switch the numbers and change the sign
a perpendicular slope to -20/-26 is 26/20.
Answer:
The image is blurry on my screen
Step-by-step explanation:
I don't know I just need the points Lol sorry